Imaging in Inflammatory Bowel Disease Mucosal Healing in Ulcerative Colitis: Relevance for Clinical Outcomes - Schirbel, Anja; Sturm, Andreas (Current Drug Targets, 2012)
There is growing evidence of the importance of mucosal healing (MH) in ulcerative colitis, but whether or not it should be a future primary treatment goal is still under intense discussion. Within the last decade many clinical trials have focused not only on response and remission rates but also on achievement of MH, while in clinical practice we still make treatment decisions on the basis of clinical symptoms. There is so far no internationally accepted definition of MH and the tools for assessment of MH vary from biomarkers to endoscopy with histological evaluation on the basis of several different scores and indices. This review will focus on present data dealing with methods to assess MH and the importance of MH for the future course of disease, the need for colectomy or risk of developing colorectal cancer and the patient’s quality of life. Many questions remain: How and when do we best assess MH? How rapidly do we need to achieve MH? What is the optimal time point to discontinue treatment after achieving MH? Well defined prospective studies are needed to address these important questions.
Keywords: inflammatory bowel disease